Cesarean scar ectopic partial molar pregnancy: A case report and a review of literature - Rania Al-Bataineh; Shireen Rawashdeh; Leen N. Lataifeh; Saja M. Alzghoul; Ahmed H. Al Sharie; Rawan Obeidat; Omar F. Altal (Case Reports in Women's Health, 2023)
A scar ectopic pregnancy exhibiting hydatidiform features is an extremely rare and clinically challenging entity. Delayed diagnosis and failure to treat such cases promptly can lead to devastating consequences. In this report, we present a case of cesarean scar ectopic partial molar pregnancy in a 37-year-old woman who presented with complaints of vaginal discharge with streaks of blood and lower abdominal pain. Diagnostic laparoscopy revealed an abnormal mass of brown soft tissue in the anterior wall of the uterus, measuring 13.0 × 9.0 × 2.0 cm, raising suspicion (in the context of elevated serum human chorionic gonadotropin levels) of a scar ectopic pregnancy. Open laparotomy was performed, and the scar ectopic mass was successfully removed. The histologic examination of the tissue revealed a partial hydatidiform mole. The patient experienced a full recovery postoperatively, with serum human chorionic gonadotropin levels gradually declining to normal values. This report is unique in its presentation of the clinicopathological features of cesarean scar ectopic molar pregnancy and the successful management of the condition.